Plant-Mycorrhizal Fungi Interactions in Phytoremediation of Geogenic Contaminated Soils - Ma, Ying; Ankit,; Tiwari, Jaya; Bauddh, Kuldeep (Frontiers in Microbiology, 2022)
Soil contamination by geogenic contaminants (GCs) represents an imperative environmental problem. Various soil remediation methods have been successfully employed to ameliorate the health risks associated with GCs. Phytoremediation is considered as an eco-friendly and economical approach to revegetate GC-contaminated soils. However, it is a very slow process, as plants take a considerable amount of time to gain biomass. Also, the process is limited only to the depth and surface area of the root. Inoculation of arbuscular mycorrhizal fungi (AMF) with remediating plants has been found to accelerate the phytoremediation process by enhancing plant biomass and their metal accumulation potential while improving the soil physicochemical and biological characteristics. Progress in the field application is hindered by a lack of understanding of complex interactions between host plant and AMF that contribute to metal detoxification/(im)mobilization/accumulation/translocation. Thus, this review is an attempt to reveal the underlying mechanisms of plant-AMF interactions in phytoremediation.